Impact of Non-performing Loans on Profitability: Evidence from Licensed Commercial Banks in Sri Lanka - Anandasayanan, S.; Gowsalya, S. (Sri Lanka Finance Association., 2023)
Non-performing loans are financial assets that do not produce any interest or principal repayment for the banks. To ensure financial stability, financial intermediaries should minimize their non-performing loans. The focus of this study is to find out the impact of non-performing loans on the profitability of licensed commercial banks in Sri Lanka. All licensed commercial banks are considered for the study. Especially 17 licensed commercial banks are taken as samples from 2014 to 2021. Descriptive statistics, correlation, multiple regression analysis, and the Hausman test were used to analyze the collected secondary data. In this study, a non-performing loan is measured by the non- performing loan ratio, considered an independent variable, and profitability is measured by return on assets and return on equity; these are used as dependent variables. To improve the accuracy and reliability of the tests, liquidity, capital adequacy ratio, and Firm size are used as control variables. According to the correlation of the study Non-performing loan ratio, the Capital adequacy ratio has a negative relationship with ROA, and liquidity has a positive relationship with ROA. Furthermore, the Non-performing loan ratio has a negative relationship with ROE; liquidity has a positive relationship with ROE. Based on regression analysis, this study found that the Non-performing loan ratio and capital adequacy ratio have a significant negative impact on profitability. However, Liquidity and Firm size have an insignificant impact on profitability. This study provides insight to commercial banks and other stakeholders on the impact of non-performing loans on the profitability of licensed commercial banks in Sri Lanka.
Keywords: Capital adequacy ratio; Firm size; Liquidity; Non-performing loans; Profitability